Fungos derivados da Antártica: biodiversidade e produção de enzimas lignocelulóticas a baixas e médias temperaturas - Barato, Mariana Blanco [UNESP] (2014)
The interest in microorganisms, especially fungi derived from underexplored environments such as Antarctica has increased in recent decades. Antarctica ecosystems have characteristics of extreme temperature, salinity or pH which prevents the development of many forms of life, being the micro-organisms the best adapted to proliferate in substrates of this continent. Microorganisms that grow in Antarctic ecosystems are able to produce cold adapted enzymes, which have potential application in many sectors of economic importance. This project is associated with the FAPESP Project 2010/17033-0 entitled “Biotechnological Exploitation of fungi derived from Antarctica, coordinated by Prof. Dr. Lara Sette and aims to know the biodiversity, to select filamentous fungi with lignocellulolytic potential and to evaluate the production of these enzymes at low and medium temperatures. For this purpose, we used 160 isolates recovered from marine and terrestrial samples of the Antarctic continent that have been maintained in the research collection of DRM (CPQBA/UNICAMP) and in the Microbial Resource Center of UNESP (CRM-UNESP). After the first screening (on solid medium and in liquid medium), two fungi were selected for subsequent experiments, one from marine sample (P1) and another one from terrestrial sample (M7), which were identified as Cadophora luteo-olivacea and Cadophora malorum, respectively. The assays regarding the evaluation of different factors in the production of ligninases allowed the identification of the effects of each variable on the enzyme activity. However, the optimization of laccase production by Cadophora luteo olivacea P1 was not efficient because the low activity of this enzyme under the conditions studied. In lignocellulosic substrates the fungus C. malorum M7 presents the best xylanase activity when grown on sugarcane bagasse and corn cobs. Among the 160 filamentous fungi studied, 76 were taxonomically characterized...